The world’s landscapes system and its change - Alekseev, Boris A.; Golubev, Genady N. (ERDKUNDE, 2000)
A 1:15,000,000 map of ’Geographic Belts and Zonal Types of Landscapes in the World’ (Lukashova 1988) was used by the authors to look into the principal features of the world landscapes structure. The world landscapes system contains 13 geographic belts, 37 landscape zones, 96 zonal types of landscapes and 61 altitudinal spectra. It represents the time in the Earth’s evolution just before the beginning of massive anthropogenic pressure. On the basis of the map, a planetary model of the geographical zonality was built as a generalised continent representing the distribution of land, the boundaries of the geographic belts and the position and areas of the zonal types of landscapes. This model is a useful reference point to observe and assess the global environmental change. A comparison with the present-day situation has demonstrated that all major global change problems associated with the landscape issues can be clearly seen and measured, using the generalised continent as a tool. Out of 96 zonal types of landscapes in the world, about 40 are modified or disappeared due to the anthropogenic pressure. It is also seen on the generalised continent that the major man-made changes are where the natural diversity of landscapes is the highest.